Imploding the racialized and patriarchal beauty myth through the critical lens of Toni Morrison's The bluest eye - Burcar, Lilijana (Vestnik za tuje jezike, 2017)
This contribution investigates and lays bare the ideological workings of racialized beauty myth as presented in Toni Morrison's The Bluest Eye by bringing together feminist theory and postcolonial theory of race. It demonstrates that racialized beauty norms are informed by both the constructs of gender and race, and that they serve as a tool of social positioning and social control in Western capitalist patriarchies. This kind of contextual understanding, which Morrison's The Bluest Eye helps to foster on a number of structurally interlocked levels, is also of crucial importance for the understanding of the way beauty myth operates today in the context of globally exported Western beauty industry. Its basic tenets remain firmly rooted in the construction and perpetuation of racialized and gendered otherness, which is why The Bluest Eye remains an eye-opener and therefore a novel of lasting value for readers in general and, as this contribution demonstrates, for students of English literature in particular.
Keywords: Afro-American literature; Morrison, Toni, 1931-; American novel; "The bluest eye"; beauty myth; afro-ameriška književnost; ameriški roman; postcolonial theory; feminist theory; mit lepote; postkolonialna teorija; feministična teorija